DOES BOARD COMMISSIONERS’ DIVERSITY MATTER IN WATER DISCLOSURE? EVIDENCE FROM INDONESIA STATE-OWNED ENTERPRISES - Manihuruk, Natal; Nurmayanti M, Poppy; Mela, Nanda Fito (Universitas Riau, 2025)
This study examines whether board commissioners’ diversity—specifically gender, educational level, and age—matters in disclosing water-related information within Indonesian state-owned enterprises during the 2019–2023 period. Utilizing panel data multiple regression analysis, the research aims to determine whether diverse board characteristics influence the extent of corporate water disclosure. The results reveal that age diversity among commissioners significantly improves water disclosure, while gender diversity and educational level do not exhibit a statistically significant impact. These findings partially support agency theory, stakeholder theory, and upper echelon theory, suggesting that older commissioners may drive greater transparency due to increased compliance awareness and concern for organizational reputation. On the other hand, the absence of significant effects from gender and educational diversity highlights the possibility that regulatory compliance and corporate priorities may outweigh the influence of individual board traits. The study contributes to the ongoing discourse on corporate governance and sustainability by offering practical implications for companies seeking to enhance their environmental reporting, as well as for investors evaluating environmental and social governance (ESG) factors. Future research is recommended to classify firms based on their water-related risk exposure and to explore alternative indicators for measuring board diversity more effectively.